North America. - Darton, William, 1781-1854 (W. Darton, 1800)
Map shows the North American continent from the "Bhering Strait" to Greenland, to "Mexico or New Spain"; west and east Florida, [French] Louisiana, the United States, Baffin Bay and Hudson's Bay and Great Lakes, "River of the West," areas of Native American habitation, "Sir Fran. Drakes Har." [San Francisco Bay]. Scale not given.